Fatigue life of notch specimen under complex fatigue loading - 461988 Sung, Aun Naa (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 2002